(untitled) (Fiep Bulletin - online, 2013)
The article below is focused on the training of physical education in higher education in Brazil and departed the following question: what changes in the courses of Physical Education after the regulation of the profession? This study aims to compare the training of physical education at the college level before and after the law 9696/98. Therefore, we sought to know the historical context of the formation of Physical Education Professionals in Brazil; analyze the process of regulation of the profession and the creation of the CONFEF / CREFs and identify differences in the formation of Licensed and Bachelor in Physical Education based on new Curriculum Guidelines of the teaching of Physical Education, approved by the CNE / MEC. The methodology adopted for the development of this research came from the qualitative literature review of works that address this topic. With this it was possible to see that among other benefits, after the regulation of the profession, the training of physical education achieved improvements especially in the delimitation of the fields, where the Licensed Professionals are trained to act exclusively in teaching this subject in Basic Education (schools), while the Alumni Professionals are trained to work in other niches of human physical activities (clubs, businesses, hospitals, gyms, etc.), but can not act Basic Education.